A first-in-human phase 1 study of cavrotolimod, a TLR9 agonist spherical nucleic acid, in healthy participants: Evidence of immune activation - Daniel, Weston L.; Lorch, Ulrike; Mix, Scott; Bexon, Alice S. (Frontiers in Immunology, 2022)
Tumor immunotherapy is designed to control malignancies through the host immune response but requires circumventing tumor-dysregulated immunomodulation through immunostimulation, relieving immunorepression, or a combination of both approaches. Here we designed and characterized cavrotolimod (formerly AST-008), an immunostimulatory spherical nucleic acid (SNA) compound targeting Toll-like receptor 9 (TLR9). We assessed the safety and pharmacodynamic (PD) properties of cavrotolimod in healthy participants in a first-in-human Phase 1 study under protocol AST-008-101 (NCT03086278; https://clinicaltrials.gov/ct2/show/NCT03086278). Healthy participants aged 18 to 40 years were enrolled to evaluate four dose levels of cavrotolimod across four cohorts. Each cohort included four participants, and all received a single subcutaneous dose of cavrotolimod. The dose levels were 5, 10, 12.5 and 18.8 μg/kg. Cavrotolimod was well tolerated and elicited no serious adverse events or dose limiting toxicities at the doses tested. The results demonstrated that cavrotolimod is a potent innate immune activator, specifically stimulating Th1-type immune responses, and exhibits PD properties that may result in anti-tumor effects in patients with cancer. This study suggests that cavrotolimod is a promising clinical immunotherapy agent.